Effects of Kr and Xe ion irradiation on the structure of Y2O3 nanoprecipitates in YBCO thin film conductors. Issue 35 (12th December 2018) - Suvorova, Elena I.; Uvarov, Oleg V.; Ovcharov, Alexey V.; Karateev, Igor A.; Vasiliev, Alexandr L.; Skuratov, Vladimir A.; Buffat, Philippe A.
ABSTRACT: The response of Y2 O3 nanoprecipitates in a 1-µm YBa2 Cu3 O7-x layer from a superconducting wire Ag/YBCO/buffer metal oxides/Hastelloy to 107 MeV Kr and 167 MeV Xe ion irradiation was investigated using a combination of transmission electron microscopy, diffraction and X-ray energy-dispersive spectrometry. The direct observation of the radiation-induced tracks in Y2 O3 nanocrystals is reported for the first time to the authors' best knowledge. Structureless damaged regions of 5–9 nm (average 8 nm) in diameter were observed in Y2 O3 nanocrystals when the electronic stopping power Se was about or higher than 4.7 keV/nm. This value of Se is the upper estimate of the minimum electronic stopping power to create damage in yttria nanocrystals. The electron diffraction patterns, high-resolution transmission electron microscopy, high-resolution scanning transmission electron microscopy, Fourier transform patterns from areas extending a few nanometres around the tracks show that yttria and YBCO keep their respective cubic and orthorhombic pristine structures.